Cardiofacioneurodevelopmental syndrome: Report of a novel patient and expansion of the phenotype. Issue 8 (22nd April 2022) - Abdalla, Ebtesam; Alawi, Malik; Meinecke, Peter; Kutsche, Kerstin; Harms, Frederike L.
Abstract: The cardiofacioneurodevelopmental syndrome (CFNDS) is characterized by craniofacial anomalies including bilateral cleft lip and palate, cardiac, skeletal, and neurodevelopmental features and additional variable manifestations. Whole‐exome sequencing revealed homozygous loss‐of‐function variants in CCDC32 (alternative name: C15orf57 ) in both previously described patients. ccdc32 deletion in zebrafish suggests a ciliary contribution to the pathomechanism. We report a 9‐year‐old female patient with CFNDS caused by a homozygous 32, 583‐bp deletion affecting CCDC32 . Independent of the affected CCDC32 transcript variant this deletion likely leads to loss of the encoded protein. The patient had intellectual disability, marked hypertelorism, bilateral cleft lip and palate, and short stature. She had bilateral conductive hearing loss, small hands and feet, and finger abnormalities. Brain imaging disclosed hypoplastic corpus callosum. We describe a core phenotype comprising developmental delay and bilateral cleft lip and palate in the three individuals with CFNDS. Variable abnormalities of the face, brain, heart, fingers, and toes and postnatal growth retardation or microcephaly can be present. Possible involvement of the uncharacterized CCDC32 protein in the adapter protein 2 (AP2) complex regulating clathrin‐mediated endocytosis has been reported. Cleft palate and cardiac defects observed in mice deficient of different AP2 subunits support a CCDC32 function in the AP2 complex.